Effects of cognitive training with additional physical activity compared to pure cognitive training in healthy older adults - Rahe J (Dove Medical Press, 2015)
Julia Rahe,1 Annette Petrelli,1 Stephanie Kaesberg,2 Gereon R Fink,3 Josef Kessler,3 Elke Kalbe1 1Psychological Gerontology and Center for Neuropsychological Diagnostics and Interventions, Institute of Gerontology, University of Vechta, Vechta, Germany; 2Cognitive Neurology Section, Institute of Neuroscience and Medicine, Research Center Jülich, Jülich, Germany; 3Department of Neurology, University Hospital Cologne, Cologne, Germany Introduction: Cognitive training (CT) has been reported to improve cognition in older adults. Its combination with protective factors such as physical activity (CPT) has rarely been studied, but it has been suggested that CPT might show stronger effects than pure CT.Materials and methods: Healthy older adults (aged 50–85 years) were trained with CPT (n=15) or CT (n=15). Interventions were conducted in 90-minute sessions twice weekly for 6.5 weeks. Cognitive functions were assessed before and immediately after the interventions, and at 1-year follow-up.Results: The main finding was an interaction effect on attention, with comparable gains from CPT and CT from pre- to post-test, but stronger effects of CPT to follow-up (P=0.02). Significant effects were found in subjects in terms of cognitive state (P=0.02), letter verbal fluency (P=0.00), and immediate (P=0.00) and delayed (P=0.01) verbal memory. Post hoc analyses indicated that these latter domains were affected differentially by CPT and CT. No significant between-subject effects were found.Conclusion: Our results suggest that CPT might lead to stronger long-term effects on attention. However, as the difference between CT and CPT was only evident at follow-up, these effects cannot be interpreted as a direct consequence of CPT; they may have been related to sustained physical activity after the training. Other domains were improved by both interventions, but no typical pattern could be identified. Possible underlying mechanisms are discussed, and directions for future research are suggested. Keywords: combined intervention, cognitive aging, exercise